The effect of neighborhood social cohesion on life satisfaction in type 2 diabetes mellitus patients: the chain mediating role of depressive symptoms and sleep quality - Ma, Xueping; Bai, Wei; Yu, Fan; Yang, Fan; Yin, Jiaxin; Shi, Huilian; Niu, Yang; Wang, Liqun (Frontiers in Public Health, 2023)
Objective: Although most studies have shown that neighborhood social cohesion (NSC) is associated with life satisfaction among patients with type 2 diabetes mellitus (T2DM), it remains unclear how NSC is linked to life satisfaction. The present study aims to examine the potential mediation effect of depressive symptoms and sleep quality on the relationship between NSC and life satisfaction among Chinese individuals with T2DM. Methods: A cross-sectional survey was conducted from August 2019 to November 2020 involving 1747 T2DM patients. The main information was obtained using the Center for Epidemiological Survey Depression Scale (CES-D), self-report sleep quality and life satisfaction questionnaire and NSC scales. Mediation analyses were performed using the PROCESS macro in SPSS. Results: The results manifested that the NSC was positively associated with sleep quality (r=0.219) and life satisfaction (r=0.214), while negatively correlated with depressive symptoms (r=-0.232). Depressive symptoms were found to be negatively associated with life satisfaction (r=-0.263). NSC influenced life satisfaction through three mediating pathways: (a) depressive symptoms (effect = 0.0081); (b) depressive symptoms and sleep quality (effect = 0.0019); and (c) sleep quality (effect = 0.0015).The total mediating effect accounted for 28.1% of the overall effect.Our findings support the hypothesis that depressive symptoms and sleep quality mediated the relationship between NSC and life satisfaction in patients with T2DM. It is important to encourage T2DM patients to participate in social interactions and enhance their level of NSC. Additionally, efforts should be made to actively reduce depressive symptoms and improve sleep quality, so as to improve their life satisfaction.